Identification of the main dyestuffs obtained from Kermes (Kermes vermilio) in the Northwest of Turkey - AYAZ SEYHAN, SERAP (OVIDIUS UNIV PRESS, 2019)
Dyer's kermes (Kermes vermilio) is found only on the kermes oak (Quercus coccifera L). They were used in the past for the preparation of dyes for textiles and as a pharmaceutical. The main constituents of this insect are kermesic acid (ka) and flavokermesic acid (fk). Historically and culturally important dyer's kermes insect red dyes were investigated by high performance liquid chromatography. Kermes in the Northwest of Turkey were analyzed first time the relative amount of the dyestuffs although their presence has been reported analytical works related to this insect. The relative amount in the acid hydrolyzed extract of Kermes vermilio from the Northwest of Turkey looked very similar to the France.
Keywords: flavokermesic acid; HPLC; kermesic acid; kermes insect; natural dyes